PENGARUH PENGEMBANGAN KARIR, PELATIHAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. GUNAWAN FAJAR - Azizah, Dita Nur; Syahputra, Erwin; Hardiningrum, Iing Sri (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARIDO - 10.32503/ammer.v2i03.3428, 2023)
The purpose of this study was to explain the significant influence of career development, job training and organizational culture on the performance of PT. Gunawan Fajar partially and simultaneously. The type of research used is quantitative research with a causality approach with a population of 85 employees of PT Gunawan Fajar. Data obtained from the results of questionnaires and research object surveys. Based on research showing that there is a significant influence partially and simultaneously between career development, training and organizational culture on the performance of employees of PT. Gunawan Dawn. Suggestions for future researchers should expand the research variables so that they can produce better research. This is proposed because it has been proven that career development, training and organizational culture variables have an effect of only 44.1% on employee performance. And there are still other variables that have not been studied in this study, namely 55.9% such as recruitment, selection, motivation and others